Pemanfaatan Media Filter Kearifan Lokal dalam Meningkatkan Kualitas Air dengan Proses Filtrasi - G M Saragih; Hadrah Hadrah; Herman Herman (Universitas Batanghari Jambi, 2021)
The need for clean water continues to increase with changing times and the passage of time, however, clean water that is suitable for consumption is not easily available in some areas, considering that the physical conditions of regional geomorphology and hydrology have different forms. Water that is suitable for drinking must be clean and minimal from pollutant loads and substances that can interfere with the health of the body, this is different from the water obtained by people in Rantau Karya Village, Geragai District, Tanjung Jabung Timur Regency, because the hydrological conditions of the area are dominated by peatlands so that the water consumed is included in peat water, where the majority of the people use dug well water, therefore a simple technology is needed in dug well water treatment by utilizing local wisdom filter media. The results showed the efficiency of removal of organic substances (KMnO4) where the initial parameter was 22.5 mg / l to be 11.218 mg / l. The efficiency of turbidity reduction is 56%, where the initial result of the turbidity parameter is 31 NTU and the final result is 15 NTU, and the final pH of well water is 6.26, where the initial test shows the number 5.6. Each thickness of the filter media to get optimum results with a thickness of 15 cm.